Shaped-charge treatment effects accompanying the formation of hard structure and new phase states in coatings on titanium - Kanzamanova, Gulzara (Behavior of materials under impact, explosion, high pressures and dynamic strain rates)
This paper presents the results of research on superhard coatings obtained by the interaction of high-speed powder clouds with a titanium substrate. High-speed powder clouds were obtained under conditions of a shaped-charge explosion. Shaped-charge synthesis was conducted using specially prepared mixtures containing atoms of nitrogen, carbon, and boron. The interaction of the initial mixture components and the substrate material yielded nitride, carbonitride, and boride phases that formed superhard coatings. The relationship between the mechanical properties of the investigated coatings and their structural state was established in this study. The specific features of the obtained layers were determined by the fact that they are multiphase coatings built into the crystalline structure of the titanium substrate. The microhardness of these layers varies in the range of 11-21 GPa.